SYNTACTIC ACQUISITION ON THREE YEARS OLD CHILD (A CASE STUDY OF AHMAD DZAKY AL-FARISI) - Nurjannah, Ikke; Asridayani, Asridayani; Afrilesa, Rini (Universitas Muara Bungo, 2023)
This research analyzes about Syntactic Acquisition of three years old child at Al-Inayah Islamic Boarding School, in Jambi Province, Tebo Regency, Rimbo Bujang sub district, at Perintis village. The purposes of this research are (1) to describe types of sentences produced by a three years old child named Ahmad Dzaky Al-Farisi (2) to find out factors that affected child in obtaining his first language acquisition on three years old named child Ahmad Dzaky Al-Farisi at Al-Inayah Islamic Boarding School in perintis village, Rimbo Bujang Sub-district, Tebo Regency, Jambi province.In this research, the writer applied descriptive qualitative method theory by Moleong (2006:6) and the writer uses Participant Observational Method (SLC) to collecting the data. The data were analyzed by using referential method and distributional method, the writer also uses an informal and formal method to represent the results of the analysis.The result of the research reveals some findings showed that the child produced four types of sentences, they are: (1) Statement, (2) Imperative Sentences, (3) Interrogative Sentences, (4) Exclamation Sentences. Based on the 15 data found in this research, the writer found 9 data of interrogative sentences, 1 data of imperative sentence, 2 data of statements, and 3 data of exclamation sentences. The most dominant type of Sentence produced on three years old child by Ahmad Dzaky Al-Farisi at Al-Inayah Islamic Boarding School especially in Perintis village, Rimbo Bujang Sub-district, Tebo Regency, Jambi Province is Interrogative sentences, the types of sentence is supported by Eastwood's theory (1994:15).Based on this research, the writer found out the factor that affected child in obtaining the first language acquisition on three years old child named Ahmad Dzaky Al-Farisi. The results of this research also show that the factor affected the first language acquisition of this child's language is Language Acquisition Devices that have innate abilities from birth which are then honed in the form of always being invited to communicate with parents, imitating other people, the mother always provides stimulation in the form of words, phrases or sentences. Based on this research, the writer formulates the factor that affected in obtaining the first language acquisition on three years old child from Ahmad Dzaky Al-Farisi is natural factor supported by Chomsky's theory (1965:222).